(untitled) (Diametros, 2024)
This paper examines the concept of vulnerability in the context of social research ethics. An ambiguity is noted in use of this term: it may refer to an incapacity to provide informed consent to participate in a research project, or it may imply heightened susceptibility to the risk of harm. It is pointed out that vulnerability is a matter of degree, and that there are different sources and types of harm, which must be taken into account in any judgment about whether additional precautions are required to protect particular categories of research participants. Furthermore, such judgments must be sensitive to the particular context in which research is taking place. This is one of several considerations that raise questions about the desirability of the sort of pre-emptive ethical regulation that has become institutionalized in many countries over the past few decades, a form that is more appropriate to medical rather than to social research. However, this is not to deny that a concern with the vulnerability of research participants is necessary on the part of social researchers. Furthermore, it must be recognized that researchers themselves may be vulnerable to harm in the research process. Finally, some discussion is provided of the way in which a concern with vulnerability can conflict with other considerations that researchers need to take into account in doing their work. The key point is that vulnerability is a complex and controversial concept, and it requires careful handling in thinking about social research ethics.